Back to Public Transport National Movement; Light Rail Transit Accessibility in Palembang - Dian Aurelia Pramudita Insani; Eko Priyo Purnomo; Delila Putri Sadayi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The launch of the National Movement Back to Public Transportation program in South Sumatra by the Ministry of Transportation is intended as the pilot project for urban community in Indonesia to daily use the public transportation services. The pilot project is using Palembang Light Rail Transit to reduce congestion and air pollution from motor vehicles. The easy accessibility of public transportation in big cities for the public is the main focus of this national movement. This research used qualitative method by analyzing the literature review of previous researches. The result shows that the implementation of the National Movement Back to Public Transportation program needs to pay attention to some factors as safety, comfort, and reliability of the public transportation as the mass transportation. Those factors could impact on increasing the passengers of Palembang Light Rail Transit per day. Cooperation and support between the central government, the local governments, and the Indonesian Railway companies are needed to improve public transportation services, develop Light Rail Transit accessibility, and mobilize the people to use and preserve the LRT.